Nursing Practice in Primary Care and Patients' Experience of Care - Roxane Borgès Da Silva; Isabelle Brault; Raynald Pineault; Maud-Christine Chouinard; Alexandre Prud'homme; Danielle D'Amour (SAGE Publishing, 2018)
Purpose: Nurses are identified as a key provider in the management of patients in primary care. The objective of this study was to evaluate patients' experience of care in primary care as it pertained to the nursing role. The aim was to test the hypothesis that, in primary health care organizations (PHCOs) where patients are systematically followed by a nurse, and where nursing competencies are therefore optimally used, patients' experience of care is better. Method: Based on a cross-sectional analysis combining organizational and experience of care surveys, we built 2 groups of PHCOs. The first group of PHCOs reported having a nurse who systematically followed patients. The second group had a nurse who performed a variety of activities but did not systematically follow patients. Five indicators of care were constructed based on patient questionnaires. Bivariate and multivariate linear mixed models with random intercepts and with patients nested within were used to analyze the experience of care indicators in both groups. Results: Bivariate analyses revealed a better patient experience of care in PHCOs where a nurse systematically followed patients than in those where a nurse performed other activities. In multivariate analyses that included adjustment variables related to PHCOs and patients, the accessibility indicator was found to be higher. Conclusion: Results indicated that systematic follow-up of patients by nurses improved patients' experience of care in terms of accessibility. Using nurses' scope of practice to its full potential is a promising avenue for enhancing both patients' experience of care and health services efficiency.